The Close Encounters Man: How One Man Made the World Believe in UFOs by Mark O’Connell - Murphy, William (Journal of Scientific Exploration, 2018)
Though short in physical stature, Dr. J. Allen Hynek is the towering figure in the study of unidentified flying objects, an enterprise that has attracted an astounding amount of public interest and in part responsive attendant effort and investigation by governments worldwide over the last 70 years. Yet the lack of recognition accorded Hynek beyond that of his name and a few associated phrases is merely one of the many contradictions in the life and work of the man. From 1948 to 1970 he was the U.S. Air Force’s top consultant to its public Unidentified Flying Object (UFO) program, studied thousands of its cases, and figured in many of its controversies. Hynek’s The UFO Experience is arguably the best book written on the subject,[1] and he left an enduring legacy by founding the Center for UFO Studies in 1973, its publications setting a high standard for work on the subject and fostering a number of disciples and other researchers who have interacted with them over the years. Hynek’s matrix for evaluating UFO reports by “strangeness” and witness credibility allowed a determination of the probative value of those reports; his basic six-category system of reported UFO phenomena has dominated the discussion since its first publication in 1972; and the “Close Encounters” subset of that system has, along with Hynek’s rather unfortunate “swamp gas” statement, for better or worse become part of the popular lexicon. Those interested in UFOs will remember Hynek mostly as the consultant to Project Blue Book who turned his back on the USAF attempts to whitewash the subject, coming to advocate serious study of unidentified flying objects. A smaller group of academics and technical people know of the scientist Hynek, highly regarded both for tangible accomplishments in astronomy, but also as champion of interpersonal techniques and changed attitudes as to how the astronomical community conducted its efforts. Numerous university graduates will remember Hynek the teacher and administrator.